SMART MARKETING: STRATEGI PROMOSI PENGRAJIN GENTENG BERBASIS WEB MOBILE - Kasmi, Kasmi; Zahra, Fista Anisa; Muslihudin, Muhamad (STMIK Pringsewu, 2024)
The gem tile industry is an industry in Sidoharjo Village, Pringsewu District which is engaged in clay tile, and the type of tile produced is mantili tile from plain tile. However, based on the results of observations that have been made, it is known that the sales system that is carried out still uses the conventional system, starting from the ordering process, and the payment process. By going directly to the tile selling point, selling in this way takes a long time in the process of selling the product, so this system is felt to be less effective and efficient if you only rely on this method. With this method, tile sales revenue will not experience a significant increase. The methodology used in this study is to use the waterfall model because by using this method the company can have a clear and measurable system workflow sequence. From this research, the results obtained are the implementation of a website-based tile sales information system that was created to make it easier for owners to carry out product promotions and marketing effectively and efficiently, make it easier for customers to find information quickly and accurately, just by looking at the website, and make it easier when paying. Based on the results of the study and discussion of the design of a website-based gem tile sales application that was created to assist in promotion, marketing and introducing new consumers to products in the gem tile industry, and a system designed to make it easier for users to access data and information that takes place quickly, accurately, effectively and efficient.